Direitos humanos, inclusão social e o trabalho da pessoa com deficiência - Vulcano, Ana Carolina Soria (2018)
This dissertation intend to explain key and current aspects so that a disabled person can effectively enjoy fundamental labor rights, without obstacles to their accessibility and without social stigmas. The objectives are to analyze the reasons for the lack of social inclusion of people with disabilities in the job market, ponder the application of the constitutional principles of work for people with disabilities, regard the mechanisms of the constitutional right to work to promote the admission of people with disabilities. Another issue to be defined is how to adapt work relationships of people with disabilities without fundamental rights being neglected. This is a bibliographical and field research. Field research was conducted in two institutions: ICEP - Cultural, Educational and Vocational Institute of People with Disabilities in Brazil; and in the SLU - Urban Cleaning Service. A semi-structured interview was used. It was found that in the not so remote past, the person with a disability was considered incapable, unworthy of living and useless to society. It is concluded that affirmative action by itself is insufficient to achieve the material equality and social inclusion of the worker with disabilities. However, they play a major role in the awareness of society, acting in the deconstruction of prejudice, which in fact helps to mitigate discrimination of workers with disabilities, opening new paths, even if they are shy to their inclusion to work.